TECHNOLOGICAL PROCESS CAPABILITY ANALYSIS - Constanţa RĂDULESCU; Marius Liviu CÎRŢÎNĂ (Fiabilitate şi Durabilitate)
In this paper is presented a case study on the analysis of the technological process using a statistical program. To analyze the technological process it is necessary to take into account the volume of the sample. The analyzed characteristic is of a landmark that is part of the whole of a milk processing machine. Based on the summary diagram, based on the determination of the values of statistical parameters and technological process capability indices, the analysis of the technological process capability is made and conclusions are drawn regarding the process.